Policy and Governance Publications in Southeast Asia During The Period 2012–2022 : A Bibliometric Analysis - Karlina, Nina; Rusli, Budiman; Candradewini, Candradewini; Sukarno, Dedi; Muharam, Riki Satia (Jurnal Manajemen Pelayanan Publik, 2024)
The purpose of this investigation is to determine which issue in Policy and Governance Publications in Southeast Asia During The Period 2012–2022 is currently trending. To analyze the data, we extracted it from the Scopus database and ran it using R software's Bibliometrix program, which was then imported into VOSviewer. According to criteria derived from citation analysis, we have identified the most important papers, journals, authors, countries, and affiliations in Southeast Asia. Indonesia has published the greatest number of contributions, followed by Malaysia and Thailand, according to the country's scientific productivity. However, even though keywords and phrases are likely to be the most relevant subjects and findings of the research, it is possible that some of the main patterns and concerns that have been covered in the entire text are not well represented in our investigation. In addition, future studies should examine relevant research clusters for developing patterns in Bibliometric in order to provide scientific information.